History of vaccine and immunization: vaccine-hesitancy discussion in Germany in XIX century - Parodi, Alessandra; Martini, Mariano (Vaccine, 2023)
Vaccination is the most celebrated and denigrated achievement of medicine and public health - not only today, but since Edward Jenner's time (1798). In fact, the idea of injecting a mild form of "disease" into a healthy person was attacked even earlier than the discovery of vaccines. The forerunner of Jenner's vaccination with bovine lymph was the inoculation of smallpox material from person to person, which, known in Europe since the beginning of the eighteenth century, was a target of harsh criticism. The reasons for criticizing the Jennerian vaccination and its mandatory practice were medical, anthropological, biological (vaccination is not safe), religious and ethical (it is wrong to inoculate a healthy person with disease), and political (vaccination is a threat to individual freedom). As such, anti-vaccination groups emerged in England, where inoculation was adopted early, as well as overall in Europe and in the United States. This paper focuses on the lesser known debate that arose in Germany in the years 1852-53 about the medical practice of vaccination. This is an a important topic of public health that has aroused a wide debate and comparison especially in recent years and now with pandemic on Sars-Cov-2 (Covid-19) and will probably be the subject of further reflection and consideration in the coming years.